Machine Learning Based on Multi-Parametric MRI to Predict Risk of Breast Cancer - Tao, Weijing; Lu, Mengjie; Zhou, Xiaoyu; Montemezzi, Stefania; Bai, Genji; Yue, Yangming; Li, Xiuli; Zhao, Lun; Zhou, Changsheng; Lu, Guangming (Frontiers in Oncology, 2021)
Purpose Machine learning (ML) can extract high-throughput features of images to predict disease. This study aimed to develop nomogram of multi-parametric MRI (mpMRI) ML model to predict the risk of breast cancer. Methods The mpMRI included non-enhanced and enhanced T1-weighted imaging (T1WI), T2-weighted imaging (T2WI), apparent diffusion coefficient (ADC), Ktrans, Kep, Ve, Vp. Regions of interest were annotated in an enhanced T1WI map and mapped to other maps in every slice. 1,132 features and top-10 principal components were extracted from every parameter map. Single-parametric and multi-parametric ML models were constructed via 10 rounds of 5-fold cross-validation. The model with the highest area under the curve (AUC) was considered as the optimal model and validated by calibration curve and decision curve. Nomogram was built with the optimal ML model and patients’ characteristics. Results This study involved 144 malignant lesions and 66 benign lesions. The average age of patients with benign and malignant lesions was 42.5 and 50.8 respectively, which were statistically different. The sixth and fourth principal components of Ktrans had more importance than others. The AUCs of Ktrans, Kep, Ve, Vp, non-enhanced T1WI, enhanced T1WI, T2WI, and ADC models were 0.86, 0.81, 0.81, 0.83, 0.79, 0.81, 0.84, and 0.83 respectively. The model with an AUC of 0.90 was considered as the optimal model which was validated by calibration curve and decision curve. Nomogram for the prediction of breast cancer was built with the optimal ML models and patient age. Conclusion Nomogram could improve the ability of breast cancer prediction preoperatively.